A strategic framework for determining technological learning performance in Chinese firms. (27th December 2010) - Xie, Wei; White, Steven
With technological leadership in most industries still held by firms in developed countries, most firms in developing countries must import technology as part of upgrading their technological capabilities. In China, some firms have achieved significant competitiveness and performance even in global markets, based on rapid technological catch-up, whereas others have failed in the face of even domestic competition. How can such differences in learning performance outcomes be explained? This paper proposes a framework as part of addressing this gap in the literature and also suggests factors that should be of interest to managers, policymakers and scholars concerned with the role of imported technologies on national development.